2021
DOI: 10.1002/jeq2.20228
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of low‐disturbance dairy manure incorporation on ammonia and greenhouse gas fluxes in a corn silage–winter rye cover crop system

Abstract: Manure and fertilizer applications contribute to greenhouse gas (GHG) and ammonia (NH 3 ) emissions. Losses of NH 3 and nitrous oxide (N 2 O) are an economic loss of nitrogen (N) to farms, and methane (CH 4 ), N 2 O, and carbon dioxide (CO 2 ) are important GHGs. Few studies have examined the effects of low-disturbance manure incorporation (LDMI) on both NH 3 and GHG fluxes. Here, NH 3 , N 2 O, CH 4 , and CO 2 fluxes in corn (Zea mays L.)-winter rye (Secale cereale L.) field plots were measured under fall LDMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…They showed surface applied manure had 1.9-and 4.3-fold greater NH 3 -N concentrations compared to incorporation (soil aeration or injection). In a recent low-disturbance manure study, Sherman et al [12] showed that 35.5% of manure applied NH 4 -N for a corn silage system was lost as NH 3 emissions compared to 0.11 and 4.5% with strip-till injection or shallow disc injection, respectively. These studies demonstrate the importance of adequate incorporation and manure-to-soil contact for capturing more NH 4 + and reducing NH 3 emissions.…”
Section: Influence Of Manure Incorporation On Nh 3 -N Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed surface applied manure had 1.9-and 4.3-fold greater NH 3 -N concentrations compared to incorporation (soil aeration or injection). In a recent low-disturbance manure study, Sherman et al [12] showed that 35.5% of manure applied NH 4 -N for a corn silage system was lost as NH 3 emissions compared to 0.11 and 4.5% with strip-till injection or shallow disc injection, respectively. These studies demonstrate the importance of adequate incorporation and manure-to-soil contact for capturing more NH 4 + and reducing NH 3 emissions.…”
Section: Influence Of Manure Incorporation On Nh 3 -N Concentrationsmentioning
confidence: 99%
“…Other studies indicate that NH 3 loss associated with manure application can vary widely (40 to 95%) depending on specific tillage implements and other factors (manure type, soils, weather) [5][6][7][8][9][10]. Low-disturbance methods, including shallow disc injection and band application/aeration, may also be effective, with shallow disc injection generally more effective for reducing soluble N and phosphorus concentrations in surface runoff [6,7,[11][12][13]. Huijsmans et al [6] summarized studies from the Netherlands and determined that surface incorporation by various tillage methods and injection reduced NH 3 volatilization compared to surface application by 75 and 95% on average, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Day 1 measurements started immediately (Time 0) with successive periods starting approximately 1, 3, and 8 h (overnight) after application, followed by two 5-h measurements during Day 2 and a 10-h period on Day 3 (no overnight). Overnight emission between Day 2 and Day 3 was estimated from linear interpolation adjusted for measured temperature and wind conditions [37,41].…”
Section: Ammonia and Ghg Sampling And Analysismentioning
confidence: 99%
“…Although initial assessment of the new systems' performance could be estimated using the approaches of life cycle assessment (LCA), or a process-based model, such as the denitrification-decomposition model (DNDC) [30], side-by-side field experiments comparing GHG emissions among different cropping systems should still be carried out. This will accurately assess the NH 3 and GHG emissions of these new cropping systems in order to establish optimal feed cropping systems in the NCP [13,[31][32][33].…”
Section: Introductionmentioning
confidence: 99%